Understanding Salafis, Salafism and modern Salafism - Mohamed Ali, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The use of the term Salafism in modern times is ambiguous and confusing in many ways. This ambiguity can be realized when many Salafis themselves are not entirely clear as to what Salafism entails, assuming that it is simply to follow the Quran and Sunnah – a problematic definition since it implies that others do not. Furthermore, due to the ambiguity of the term, Salafism in an actual broader sense is claimed by all Muslims, in that the universal Islamic ideal is to imitate the Prophet and the early Muslim community. This paper provides an understanding on the world of Salafism, particularly the phenomenon of modern Salafism. It begins with a brief definition of Salafism, its history and attempts to discuss its realities and complexities in the modern world. The paper also highlights the various groups and categories of modern Salafis as observed by several academics and commentators. It concludes with an analysis of the ideology, characteristics and components of modern Salafism.